Development of Geometry Module Based on Computational Thinking Assisted by GeoGebra - Heni Lilia Dewi; Santika Lya Diah Pramesti (Jurusan Tadris Matematika UIN Siber Syekh Nurjati Cirebon, 2023)
This study aims to produce valid and feasible geometry module development research integrated computational thinking assisted GeoGebra. This research uses a type of R&D research that contains three stages, namely (1) (define), (2) (design), and (3) (develop). The research subjects were students in Tadris Matematika FTIK IAIN Pekalongan. Data collection techniques were carried out by conducting observations, questionnaires, and learning outcomes tests. The data analysis techniques used were analysis of the validity of teaching materials, analysis of test items, analysis of feasibility of the module, and analysis of the effectiveness of the module. The results showed that the developed module: (1) valid, after going through the validation process, (2) feasible, because there is a good response about the mathematics teaching materials integrated computational thinking assisted by GeoGebra from students and teachers, and (3) effective, by considering because students' mathematical abilities increase through a geometry module integrated computational thinking assisted by GeoGebra